Hospital burden of pneumococcal disease in Spain (2016–2022): A retrospective study - Ruth Gil-Prieto; Valentín Hernandez-Barrera; Patricia Marín-García; Alba González-Escalada; Ángel Gil-de-Miguel (Human Vaccines & Immunotherapeutics)
Pneumococcal disease is a leading cause of morbidity and mortality worldwide. From 2016 to 2022, 358,603 hospitalized patients were identified as having pneumococcal disease. The overall annual hospitalization rate was 108.9 hospitalizations per 100,000 people, which significantly increased with age, reaching 748.0 hospitalizations per 100,000 among those aged ≥90 years. The hospitalization rates for pneumococcal pneumonia, meningitis, and sepsis were 25.4, 0.7, and 3.5 hospitalizations per 100,000 people, respectively, reaching the highest rates in those ≥90 years of age for pneumococcal pneumonia and sepsis, with 241.6 and 22.0 hospitalizations per 100,000 people, respectively, and in those <1 year of age for meningitis, with 3.4 hospitalizations per 100,000 people. The total number of deaths among all hospitalized pneumococcal infection patients was 51,668, with a total case fatality rate of 14.4%. The case fatality rates for pneumococcal pneumonia, meningitis, and sepsis were 7.9%, 10.6%, and 19.8%, respectively. The case fatality rate increased dramatically with age. Most patients presented with at least one underlying condition. The case fatality rate among patients with at least one comorbidity was significantly higher (p < .05) than that among patients without underlying conditions (16.0% vs. 3.2%, respectively), with a fivefold greater probability of death (OR = 5.7). During this period, the annual cost of hospitalizations for the health system exceeded EUR 383 million. Thus, the use of new broad-spectrum PCVs and improved vaccination protocols for elderly individuals and people with comorbidities could help reduce the high hospital burden of disease and mortality due to pneumococcal infection in our country.